2005
DOI: 10.1080/09593980500321085
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Metronome® training for a 9-year-old boy with attention and motor coordination difficulties

Abstract: The purpose of this case report is to describe a new intervention, the Interactive Metronome, for improving timing and coordination. A nine-year-old boy, with difficulties in attention and developmental delay of unspecified origin underwent a seven-week training program with the Interactive Metronome. Before, during, and after training timing, accuracy was assessed with testing procedures consistent with the Interactive Metronome training protocol. Before and after training, his gross and fine motor skills wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…The notion that physical exercise may improve physiological and biobehavioral markers in ADHD has some support (Bartscherer and Dole 2005;Trocki-Ables et al 2001). Several studies have addressed the neurobehavioral effects of exercise upon animal models of ADHD (Hopkins et al 2009;Naylor et al 2005).…”
Section: Physical Exercise In Adhdmentioning
confidence: 98%
“…The notion that physical exercise may improve physiological and biobehavioral markers in ADHD has some support (Bartscherer and Dole 2005;Trocki-Ables et al 2001). Several studies have addressed the neurobehavioral effects of exercise upon animal models of ADHD (Hopkins et al 2009;Naylor et al 2005).…”
Section: Physical Exercise In Adhdmentioning
confidence: 98%
“…This sparse literature includes individual case studies (Koomar et al, 2001;Bartscherer and Dole, 2005;Sabado and Fuller, 2008), unpublished studies (Diamond SJ, 2003, unpublished observation;Gorman, 2003, unpublished observation), and unpublished meeting abstracts (Stemmer, 1997;Jones, 2004). There are only two peer-reviewed studies comparing pretreatment and posttreatment effects that include a control group, and one of these found that the Interactive Metronome improved golf swings in healthy normal individuals (Libkuman and Otanie, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…A new intervention called Interactive Metronome (IM) for improving timing and coordination was tested in a case study (Bartscherer & Dole, 2005). The IM was used by physical therapists to assess the child's timing and accuracy.…”
Section: Contemporary Physical Therapymentioning
confidence: 99%